Abbasid-Byzantine Relations during the Seljuk Era (The International Journal of Educational Sciences and Arts, 2023)
This study aims to highlight the Abbasid-Byzantine relations during the Seljuk era and to identify the early historical features of the political relations between the two countries. The study also aims to identify the origin and lineage of the Seljuks and determine the nature of the relationship between the Seljuks and the Byzantine state. In addition, it tackles the most important military battles between the two states and their most important results. In addition, to know the military power of the Seljuk state and how they prepare and arrange their military forces.The importance of this study comprises the political relations of the Seljuk state with the Byzantine state, the emergence of the Seljuks as a main military force that had a major role in changing the interior political situation of the Abbasid state and limited the political and military influence of the Byzantine state,This study relied on historical, descriptive, and analytical methods as well as a list of historical sources and references. The results demonstrate the important aspect of the exterior relations of the Seljuk state and the importance of Byzantine state power, which represented one of the major global states at that time. The study also clarifies the important aspects of the history of the two states. The results also show that the relation between the two states was not always belligerent and hostile, but rather peaceful and friendly sometimes.The most important recommendations include the interest in studying the foreign relations of the Seljuk state. Besides, the importance of studying the economic, commercial and social history of the Seljuk state to determine their role and the extent of their great civilizational contribution in the development of the history of the Islamic state.
Keywords: Abbasid-Byzantine Relations; Seljuk State; Abbasid State; Byzantine State